PERAN KEDUTAAN BESAR REPUBLIK INDONESIA KUALA LUMPUR DALAM PELAKSANAAN KERJASAMA KETENAGAKERJAAN INDONESIA – MALAYSIA STUDI KASUS : PENANGGULANGAN KASUS PENIPUAN PADA PEKERJA MIGRAN INDONESIA DI MALAYSIA TAHUN 2019 – 2021 - Maesa, Dimas Arya; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Labor cooperation between Indonesia and Malaysia has officially been carried out since 2004 with Indonesia sending the Indonesian Embassy as a diplomatic representative in Malaysia. The efforts made by the Indonesian Embassy to assist PMI abroad are by becoming a facilitator for PMI and providing job information in Malaysia, carrying out notifications on social media, and carrying out collaboration with related agencies abroad. Even so, there are still many problems that befall PMI candidates who wish to work abroad, for example PMIs who are tricked into registering to work abroad. Most PMIs are deceived because there are illegal agencies originating from abroad and working with illegal groups in the country to target Indonesian citizens, especially those who still do not know the terms and conditions that apply to be able to work abroad legally and correctly. In this study the authors use the perspective of Neo-liberalism, with the theory of Diplomacy as a basic research reference. The type of research used in this study is qualitative using phenomenological research methods. The data used is taken from the phenomenon of cases that occur, and various literature such as books, articles, and internet sites that are considered relevant to the contents of the research. The results of the research show that the Indonesian Embassy fine enough to protect PMI who had been tricked into working abroad. It has only been discovered that with the calibration program in 2020, it can be seen that there is an increase in the number of illegal PMIs in Malaysia who are exposed to wanting to return, and even wishing to be able to legally register to work again in Malaysia. Keywords : Indonesian Embassy, PMI, Fraud, Cooperation, Indonesia, Malaysia